2004
DOI: 10.1104/pp.103.037747
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Arabidopsis Homolog of Yeast Vps52p Is Required for Pollen Tube Elongation, Localizes to Golgi, and Might Be Involved in Vesicle Trafficking

Abstract: The screening of the Versailles collection of Arabidopsis T-DNA transformants allowed us to identify several male gametophytic mutants, including poky pollen tube (pok). The pok mutant, which could only be isolated as a hemizygous line, exhibits very short pollen tubes, explaining the male-specific transmission defect observed in this line. We show that the POK gene is duplicated in the Arabidopsis genome and that the predicted POK protein sequence is highly conserved from lower to higher eukaryotes. The putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 53 publications
3
66
0
Order By: Relevance
“…We also show that Arabidopsis Atg6/Vps30 partially complemented VPS function in atg6/vps30 mutant yeast. Several other Arabidopsis VPS homologs are required in pollen tubes (Hicks et al, 2004;Lobstein et al, 2004) because the polarized growth of pollen tubes requires membrane trafficking (Hepler et al, 2001;Monteiro et al, 2005). We found that disruption of AtATG6/VPS30 resulted in male sterility because the mutant pollen did not germinate.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We also show that Arabidopsis Atg6/Vps30 partially complemented VPS function in atg6/vps30 mutant yeast. Several other Arabidopsis VPS homologs are required in pollen tubes (Hicks et al, 2004;Lobstein et al, 2004) because the polarized growth of pollen tubes requires membrane trafficking (Hepler et al, 2001;Monteiro et al, 2005). We found that disruption of AtATG6/VPS30 resulted in male sterility because the mutant pollen did not germinate.…”
mentioning
confidence: 67%
“…5B). Likewise, POK/AtVPS52, another Arabidopsis VPS homolog implicated in pollen tube elongation (Lobstein et al, 2004), was expressed in different tissues and continuously expressed throughout pollen development (Lobstein et al, 2004;Fig. 5B).…”
Section: Expression Of Atg6 In Arabidopsismentioning
confidence: 99%
“…Recent genetic data confirm the importance of the Golgi for pollen tube growth. Mutations in genes encoding Golgi-localized proteins known to regulate vesicle trafficking in animal and yeast cells, such as a tobacco Rab2 GTPase (Cheung et al 2002) and an Arabidopsis homolog of yeast Vps52p (Lobstein et al 2004), are impaired in pollen tube growth. However, the mechanisms by which these proteins regulate pollen tube elongation are not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…BECLIN1, an Arabidopsis homolog of yeast Beclin1/Atg6/Vps30, which associates with VPS34 and plays a role in autophagy and vacuolar protein sorting, is expressed predominantly in mature pollen, and disruption of this gene by T-DNA insertion results in male sterility due to severely reduced pollen germination (Fujiki et al, 2007;Qin et al, 2007). VACUOLESS1 (VPS16) and POKY POLLEN TUBE (VPS52), Arabidopsis VPS homologs, also play roles in pollen tube elongation (Hicks et al, 2004;Lobstein et al, 2004). Together, these findings strongly support a central role for the PI3K-associated pathway in pollen development and/ or tube elongation.…”
Section: Discussionmentioning
confidence: 99%